2009
DOI: 10.1183/09059180.00001109
|View full text |Cite
|
Sign up to set email alerts
|

Update on the roles of distal airways in asthma

Abstract: The present review is the summary of an expert workshop that took place in Vence (France) in 2007 on the role of distal airways in asthma. The evidence showing inflammation and remodelling in distal airways, and their possible involvement in asthma control and natural history, was reviewed. The usefulness and limitations of various techniques used for assessing distal airways were also evaluated, including pulmonary function tests and imaging. Finally, the available data studying the benefit of treatment bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 159 publications
(199 reference statements)
1
50
0
5
Order By: Relevance
“…This problem can be partly solved by using i.v. gadolinium infusion or by inhalation of 3 He, which allows analysis of ventilation distribution, estimated nonventilated lung volume and percentage diseased lung. The PHIL study evaluated He-MRI findings versus HCRT findings in 29 normal volunteers and in 52 subjects with COPD and performed correlation with FEV1/FVC indicating airway obstruction, and DL,CO indicating alveolar destruction [65].…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be partly solved by using i.v. gadolinium infusion or by inhalation of 3 He, which allows analysis of ventilation distribution, estimated nonventilated lung volume and percentage diseased lung. The PHIL study evaluated He-MRI findings versus HCRT findings in 29 normal volunteers and in 52 subjects with COPD and performed correlation with FEV1/FVC indicating airway obstruction, and DL,CO indicating alveolar destruction [65].…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 99%
“…Although small airways contribute little to airway resistance in healthy subjects, studies using invasive measurement of airway resistance have shown that small airways are the major site of airflow limitation in both asthma and COPD [2]. Despite their importance, small airways have proven difficult to study [3]. Herein, I will examine current knowledge obtained by pathological and physiological measurements, and their relevance to clinical manifestations and therapeutics in asthma and COPD.…”
mentioning
confidence: 99%
“…Distal airways are usually defined as non-cartilaginous conducting airways with an internal diameter ,2 mm (approximately corresponding to eight generations of airways down to terminal and respiratory bronchioles) and alveoli. A more detailed description of the anatomy of distal airways can be found in a review article by BURGEL et al [7]. Inflammatory changes and structural abnormalities in distal airways of COPD patients have proven difficult to explore due to their localisation deep within the thoracic cavity.…”
Section: Investigating Structural Abnormalities and Inflammation In Dmentioning
confidence: 99%
“…The main difficulty is the lack of reliable and widely available lung function parameters able to detect distal airways involvement in clinical practice. A number of parameters have been proposed but most techniques, and particularly the most specific, remain confined to highly specialised lung function laboratories and none can be considered, at present, as the gold standard [3][4][5].…”
mentioning
confidence: 99%